BREAKTHROUGH ECONOMY: FEATURES OF FORMATION AND DEVELOPMENT IN RUSSIA - E. Bykovskaia; N. Kazantseva; G. Kharchilava (Вестник университета)
It has been shown, that the national economy of Russia is subject to reform and needs in innovative transformation. The information economy implies radical changes in all its spheres and affects the activities of many economic entities at different hierarchical levels of management. The directions of creation of development institutions, combining elements of self-regulation and state regulation and providing formation of breakthrough economy have been highlighted. A new breakthrough technologies of transformation of economy, along with traditional methods of managing the most priority of which are mobilizing resources in education and science-intensive industries have been considered.